Corporate sustainable development performance through top management team's transactive memory system and organizational resilience: A moderated mediation analysis - Chun-Liang Yao; Li-Yuan Wang (Heliyon, 2024)
Addressing the measurement of corporate sustainable development performance (SDP) in economic, social, and environmental dimensions is a pressing global challenge. This study investigates the intrinsic impact mechanisms of the top management team's transactive memory system (TMT TMS) on SDP within Chinese manufacturing firms. It extends the analysis by introducing opportunity alertness (OA) as a moderating variable and organizational resilience (OR) as a mediating variable. Notably, OA was found to have a moderating mediation effect on the TMT TMS-OR-SDP pathway. Data from 294 executives was collected through non-probability convenience sampling. Initially, exploratory factor analysis was conducted utilizing SPSS; confirmatory factor analysis was performed with the aid of AMOS. Additionally, hierarchical regression and the SPSS PROCESS macro were employed to test the hypothesized models and paths of influence. The results illuminate the positive impact of TMT TMS on SDP through the enhancement of OR, a relationship further strengthened by OA. This study adds to the theoretical understanding and offers practical insights for optimizing TMT TMS and OA to achieve corporate sustainable development.